Guillain–Barre syndrome: a prevalent autoimmune disease during the coronavirus disease-2019 pandemic. Issue 1 (January 2022) - Ahmadi, Mahsa; Rezaei, Zeinab; Shirazi, Fatemeh A.; Shafiei, Morvarid
Abstract : Guillain–Barre syndrome (GBS), the most frequent cause of acute paralytic neuropathy, is an inflammatory polyneuropathy that is autoimmune in nature. Many infectious agents such as Campylobacter jejuni (the most commonly identified bacteria associated with GBS), cytomegalovirus, Epstein–Barr virus, measles virus, influenza A virus, and Mycoplasma pneumonia, as well as enterovirus D68 and Zika virus and noninfectious agents such as vaccines and surgeries have been reported to trigger GBS. Three main variants of GBS include the classic acute inflammatory demyelinating polyneuropathy (AIDP), which is the most common presentation of GBS, Miller Fisher syndrome, and the recently defined axon loss variants (acute motor axonal neuropathy and acute motor and sensory axonal neuropathy). One of the assumptions about the mechanisms of GBS is molecular mimicry, which is a process caused due to the structural resemblance between a microorganism and the host. The original concept of GBS is rooted in molecular mimicry defined as the similarity between the microorganisms' peptide sequences or epitopes and ganglioside sequences or structures. Since the coronavirus disease-2019 outbreak in January 2020 there have been cases of GBS reported. Our review aims at providing an overview of some case reports of the severe acute respiratory syndrome coronavirus-2-related GBS.